Effect of wet cupping therapy on blood pressure in hypertensive patient - Dendy Kharisna; Widiya Anggraini; Yeni Devita; Angga Arfina; Roni Saputra; Rizka Febtrina (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2022)
Background : Hypertension that is not well controlled have a bad impact on the sufferer. Non-pharmacological treatment tends to be preferred by the public to control hypertension. One of the alternatives chosen to treat hypertension is wet cupping therapy. This study aimed to determine the effect of wet cupping therapy on blood pressure in hypertension. Method : This type of research is quantitative using a quasi-experimental design with one group design pre-test and post-test approach. The study was conducted at the Rumah Sehat Islamic Nurse (RSIN) Pekanbaru in May-July 2022. The number of samples used in this study was 15 respondents taken using accidental sampling techniques. The instrument in the study was in the form of a questionnaire containing the demographic data of respondents and a wet cupping device that was following the standards. Data were analyzed univariately and bivariate analysis using the Wilcoxon test. Results : The results of the Wilcoxon statistical test found that there was a significant influence before and after wet cupping therapy on systole blood pressure (p-value = 0.026) and diastole blood pressure (p-value = 0.018). The results also showed a decrease in the average of systolic blood pressure by 3.07 mmHg and diastolic blood pressure by 4.97 mmHg. Conclusion : Based on the results of the study, it can be concluded that wet cupping therapy affects systolic and diastolic blood pressure in people with hypertension. This therapy can be an alternative and complementary therapy in the treatment and control of hypertension.